Kostnadsreducering av trycksslangar med bibehållen kvalitet - Aspegren, Simon; Nilsson, Markus (My University, 2016)
The purpose with this work is to develop a high pressure hose with respect to minimise its cost without affect the user-friendliness and its quality. The hose is used to connect a heat- or cooling system to a measuring instrument which generates values that can be used when balancing the system in a way it can work in the most efficient way possible. The problem nowadays is that the hose is too expensive for being a competitive product on the market. The project on order of IMI Hydronic located in Ljung. It’s to their measuring instrument TAScope that the hoses is used. The question formulation during the project has included, where is the cost in the product and what can be done to in the most efficient way minimise these without affect the quality. The above mentioned question formulation led to a reconstruction of the hose became relevant. The reconstruction process led to three different head concepts which by the time where developed after tests and analyses of the concepts. The concepts consist of three different solutions to the connection between the hose and the quick connection. The remaining parts were then selected to fit with the selected concept. In the end one concept was selected by a selection matrix. The selected concept has not been able to be tested due to a custom made tool that was needed to produce the prototype. However, a similar concept has been tested with good test results and indicates good potential in the winning concept. By the cost analysis made, the total price of the new constructed hose had a price which is about 46% cheaper. This percentage is reached by minimising the parts of the hose and bring the assembly back to IMI’s production. The only limitations set before the start of the project was the connections which also is used to the already existing hose. These connections had to be used in the new version of the hose also. Additional costs from sales became a limitation because the work is executed on IMI’s R&D (Research & Development) who doesn’t control selling costs. Since a way to avoid the additional costs between the company which currently assemble the hose is to do the assembly yourself which became one of the goals during the project.
Keywords: Produktion; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Konstruktionsteknik; Production; Sustainable Development; Innovation & Entrepreneurship; Construction engineering